Simulation Design of PT100 Platinum Thermistor Test System - LI Xiaowen; YAN Weilin (Kongzhi Yu Xinxi Jishu)
To overcome the disability of traditional DAC digital simulation resistor which cannot change with test current, based on the current typical detection system of PT100 in rail transportation industry, it presented a simulation design of PT100 in which analog output voltage of DAC can be controlled by FPGA. With special analog circuit design, the conversion from digital signal to channel resistor is achieved in error within plus or minus 0.2 Ω. With high precision and quick speed of value refreshment, the design can meet the requirements of multiple channel PT100 detected system.